PHARMACOLOGICAL SCREENING OF ALSOTONIA SCHOLARIS - Vinod, Rathor; Shailendra, Wadhwa (Asian Journal of Pharmaceutical Research and Development, 2016)
A large number of medicinal plants are claimed to possess anthelmintic property in traditional systems of medicine and are also utilize by ethnic groups worldwide. The development of anthelmintic resistance and the high cost of conventional anthelmintic drugs led to the evaluation of medicinal plant as an alternative source of anthelmintice. In the current study were conducted to determine the possible anthelmintic and antibacterial effects of leaves of Alstonia scholaris.